PEMBERDAYAAN PEREMPUAN KEPALA KELUARGA DALAM PENINGKATAN EKONOMI KELUARGA MELALUI PROGRAM BUNDA PUSPA - Faqihatin, Faqihatin; Faizah, Nur; Ainiyah, Maslakhatul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The government plays a vital role in addressing women's issues, particularly for women heads of households who bear dual responsibilities as both caretakers and breadwinners. One strategic effort is the implementation of the Bunda Puspa Program, which is part of the 2021–2026 development plan of Gresik Regency. This program aims to increase household income, strengthen psychological and social resilience through gender equality and child rights fulfillment, and promote women's economic independence through skills training. This study aims to analyze the empowerment strategies for women in improving family economic conditions through the Bunda Puspa Program in Bungah Village. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation involving five women heads of households as informants. The study revealed four key findings: (1) active participation of women in the program; (2) the need for continuity in program implementation; (3) the importance of needs-based empowerment and strengthening of social networks; and (4) the uneven dissemination of the program across community levels. In the future, it is hoped that this empowerment strategy will be implemented sustainably, accompanied by intensive mentoring, so that women heads of households can become increasingly empowered and economically self-reliant. ABSTRAK Pemerintah memiliki peran penting dalam mengatasi persoalan perempuan, khususnya perempuan kepala keluarga yang memikul peran ganda sebagai pengelola rumah tangga dan pencari nafkah. Salah satu upaya strategis dilakukan melalui Program Bunda Puspa, bagian dari rencana pembangunan Kabupaten Gresik 2021–2026. Program ini bertujuan meningkatkan pendapatan keluarga, memperkuat ketahanan psikologis dan sosial melalui kesetaraan gender serta pemenuhan hak anak, dan mendorong kemandirian ekonomi perempuan melalui pelatihan keterampilan. Penelitian ini bertujuan menganalisis strategi pemberdayaan perempuan dalam peningkatan ekonomi keluarga melalui Program Bunda Puspa di Desa Bungah. Dengan pendekatan deskriptif kualitatif, data diperoleh dari observasi, wawancara, dan dokumentasi terhadap lima perempuan kepala keluarga sebagai informan. Hasil penelitian menunjukkan empat temuan utama: (1) partisipasi aktif perempuan dalam program; (2) perlunya kesinambungan pelaksanaan program; (3) pentingnya pemberdayaan berbasis kebutuhan dan penguatan jejaring sosial; dan (4) belum meratanya sosialisasi program di seluruh lapisan masyarakat. Ke depan, diharapkan strategi pemberdayaan ini dapat dijalankan secara berkelanjutan dengan pembinaan intensif, agar perempuan kepala keluarga semakin berdaya dan mandiri secara ekonomi.